Implementation of Islamic Religious Education Learning Evaluation Based on Project Based Learning in Merdeka Curriculum - Rahman, Abdul; Remiswal, Remiswal; Khadijah, Khadijah (Al-kayyis: Journal of Islamic Education, 2024)
The implementation of Islamic Religious Education learning evaluation based on Project Based Learning in the Merdeka Curriculum is an educational innovation that aims to improve the quality of learning through a more dynamic and student-centered approach. The purpose of the research on the implementation of the Project Based Learning -based Islamic Religious Education learning evaluation in the Merdeka Curriculum at Madrasah is to analyze and evaluate the effectiveness of the implementation of the Project Based Learning method in Islamic Religious Education learning. This research method uses descriptive quantitative. The research will involve quantitative data collection through surveys and questionnaires distributed to students and teachers at Madrasah. The questionnaires are designed to measure students' perceptions and satisfaction levels as well as the effectiveness of Project Based Learning implementation from the teachers' perspective. In addition, additional data will be collected through document analysis, such as student project results, teacher evaluation reports, and classroom observation notes. The collected data will be analyzed using descriptive statistics to describe the frequency distribution, percentage, mean, and standard deviation of the variables studied. The results of this study indicate that the implementation of Project Based Learning is effective in improving students' understanding of Islamic Religious Education teaching materials. Students are actively involved in learning, increase motivation, and develop critical, creative, and collaborative skills. Challenges such as limited resources, lack of teacher training, and difficulty designing evaluation instruments according to the Project Based Learning context were also identified. To overcome them, in-depth training for teachers, improved access to technology and learning resources, and the development of evaluation strategies in accordance with Project Based Learning are needed. By adopting the practical recommendations from this study, it is expected that the implementation of Project Based Learning -based learning evaluation can improve the effectiveness and efficiency of achieving Merdeka Curriculum goals.